Home-School Communication in Digital Era: A Bibliometric Analysis of Publications on Technology Supporting Parental Involvement in Early Childhood Education - Mashudi, Esya Anesty; Hendriawan, Deri; Sundari, Nenden; Nuroniah, Pepi; Arzaqi, Roby Naufal (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
Despite the increasing integration of digital technologies in early childhood education, there remains a significant gap in comprehensive, trend-based understanding of how these technologies support parental involvement. Existing studies often lack a systematic exploration of publication patterns, thematic focuses, and emerging innovations in this field. This study addresses that gap by analysing the scope and trajectory of research on technology that supports parental involvement in early childhood education using bibliometric review and data mapping techniques. This study examined relevant publications from 2014 to 2023 through computational mapping using VOSviewer software. Bibliometric data from 101 scholarly articles were retrieved via Harzing’s Publish or Perish software and analyzed to generate visualization maps that categorize research themes and trends. Findings indicate fluctuating but overall increasing trends in research output, with notable peaks after 2020, suggesting renewed interest in this domain, particularly following the COVID-19 pandemic. The visualization maps revealed core research themes centered around digital communication tools, parental engagement, and home-school collaboration. These findings have significant implications for future educational practices and policy development. They provide a foundation for enhancing digital strategies that foster equitable and meaningful parent-educator partnerships in early childhood education. Furthermore, they highlight the importance of addressing digital literacy gaps and promoting inclusive approaches in the design and implementation of technology-mediated parental involvement programs.